The equivalent expression is (c) [tex]9 - 3\sqrt 7 + 3\sqrt 7 - \sqrt {49}[/tex]
The difference of squares equation is given as:
[tex](a + b)(a - b) = a^2 -b^2[/tex]
And the radical expression is given as:
[tex] (3+ \sqrt 7)(3- \sqrt7)[/tex]
By comparing the above expression to [tex](a + b)(a - b) = a^2 -b^2[/tex], we have:
[tex]a =3[/tex]
[tex]b = \sqrt 7[/tex]
Substitute these values in [tex](a + b)(a - b) = a^2 -b^2[/tex]
[tex] (3+ \sqrt 7)(3- \sqrt7) = 3^2 - (\sqrt 7)^2[/tex]
This gives
[tex] (3+ \sqrt 7)(3- \sqrt7) = 9 - \sqrt {49}[/tex]
By complete expansion, we have:
[tex] (3+ \sqrt 7)(3- \sqrt7) = 9 - 3\sqrt 7 + 3\sqrt 7 - \sqrt {49}[/tex]
Hence, the equivalent expression is (c)
Read more about difference of two squares at:
https://brainly.com/question/3189867